University engagement to improve safety education. Issue 3 (11th February 2021) - Lim, Kok Hwa; Teng, Chong Seng
Abstract: With major hazards installations regulatory framework implemented in Singapore, taking effect from September 2017, the chemical and pharmaceutical industry needed to build up its capabilities to demonstrate to regulators how risks from major accident hazards in the premises can be reduced to as low as reasonably practicable. Specialist Certificate in Process Safety was initiated after discussion between Singapore Institute of Technology and Pfizer. It was established that there was a need to harmonize process safety training across the industry and a need to train process safety practitioners to build up in‐house capability to meet the new standard. After the discussion with Pfizer on their needs, a program outline was drafted and subsequently sent to Pfizer's process safety subject matter experts for comments. Upon receiving their feedback, the Process Safety Workshop Series for Pharmaceutical Industry was developed. The training pedagogy for this workshop integrated hands‐on learning at the workplace by collaborating with the company for plant walk‐throughs of relevant areas during the workshops. In addition, the fundamental topics from the workshops were integrated into the BE Pharmaceutical Engineering's Process Safety Module to ensure new engineering graduates entering the pharmaceutical industry have basic process safety skills needed by the industry.